2011
DOI: 10.1038/ng.765
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation promotes de novo targeting of HP1α to pericentric heterochromatin

Abstract: HP1 enrichment at pericentric heterochromatin is considered important for centromere function. Although HP1 binding to H3K9me3 can explain its accumulation at pericentric heterochromatin, how it is initially targeted there remains unclear. Here, in mouse cells, we reveal the presence of long nuclear noncoding transcripts corresponding to major satellite repeats at the periphery of pericentric heterochromatin. Furthermore, we find that major transcripts in the forward orientation specifically associate with SUM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
220
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(232 citation statements)
references
References 56 publications
11
220
1
Order By: Relevance
“…[25][26][27] HP1a is known to be involved in transcriptional silencing of gene poor pericentromeric heterochromatin by directly interacting with H3K9me3 present in these chromatin regions. [28][29][30] Although KDM2A has been studied with regards to regulation of pericentromeric heterochromatin, it is not clear from the published data whether the observed derepression of the pericentromeric repeats is caused by the absence of KDM2A-LF or by the absence of KDM2A-SF. 33 Our results show that KDM2A-SF accumulates at pericentromeric regions in an HP1a-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…[25][26][27] HP1a is known to be involved in transcriptional silencing of gene poor pericentromeric heterochromatin by directly interacting with H3K9me3 present in these chromatin regions. [28][29][30] Although KDM2A has been studied with regards to regulation of pericentromeric heterochromatin, it is not clear from the published data whether the observed derepression of the pericentromeric repeats is caused by the absence of KDM2A-LF or by the absence of KDM2A-SF. 33 Our results show that KDM2A-SF accumulates at pericentromeric regions in an HP1a-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…3B), a histone modification associated with transcriptionally silent heterochromatin 1,9,35 and also with HP1a (Fig. 3C), a protein associated with pericentromeric and telomeric heterochromatin, [28][29][30][31][32] 2. the KDM2A structures localize next to CENP-A (Fig. 3D), a histone variant associated with centromeric heterochromatin.…”
Section: Kdm2a-sf Forms Distinct Heterochromatic Structures In An Hp1mentioning
confidence: 99%
See 2 more Smart Citations
“…We identified that the HP1a isoform was targeted at these domains when post-translationally modified by sumoylation, even in the absence of Suv39h-dependent H3K9me3. Importantly, we revealed a specific interaction between SUMO-HP1a and pericentric RNA transcripts 7 (Fig. 1).…”
mentioning
confidence: 98%